Ideas and Networks: The Rise and Fall of Research Bodies for Powered Artificial Arms in America and Canada, 1945-1977 - Foord, David; Kyberd, Peter (Scientia Canadensis, 2015)
This paper examines the rise and fall of research and development funding programs for upper-limb myoelectric prosthetics in America and Canada from 1945 to 1977. Despite similarities in overall technological goals, to produce electronic arms and hands for veterans in the US and children with phocomelic limbs in Canada, we argue that the reasons for starting and ending the programs reflected different national preoccupations. In the US the reasons for the creation in 1945 and termination in 1977 of funding programs focused on the lack of fundamental research in the field, and role that science could have in the development and design in prosthetics. In Canada, by contrast, there was little discussion about science and its relationship to technology in knowledge creation when the prosthetics research and training unit (PRTU) funding program was founded in 1963 and wound up in 1975. Instead, the policy discussion focused on the importance of regional representation and relationships among different professional groups and sectors of society.